To Spurn, Burn or Return…that is the Concern. Review of Wasteland, by Oliver Franklin-Wallis - Venkatesh, G (Studia Ecologiae et Bioethicae, 2024)
The review concerns Oliver Franklin-Wallis’s Wasteland, a comprehensive exposition on the global production, management and revalorisation of waste. It delineates the contrast between unregulated dumping sites and engineered sanitary landfills, emphasising both the energy recovery potential and environmental considerations of waste-to-energy technologies. Subsequently, the assessment highlights the virtues of a circular economy through the “Rs” – from reduction to remanufacturing – and illustrates pioneering recycling and upcycling initiatives across diverse geographic contexts. The review concludes with a call for deliberate consumption curtailment and the adoption of waste-minimising strategies, regarded as imperative for achieving long-term sustainability.